Evaluating integrated learning: A SECI model approach through importance-performance analysis - Muhammadan, Sabda Alam; Ma'arif, Mochamad Syamsul; Suhendi, Suhendi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study evaluates the integration of learning models within the Ministry of Finance of Indonesia, using the SECI model as a theoretical framework to assess knowledge management practices. The research addresses the urgent need for effective knowledge integration in public sector organizations, particularly in light of the Ministry’s adoption of the 70:20:10 learning model. The primary objective is to analyze the alignment of this model with the SECI framework and identify areas for improvement in knowledge management practices. A quantitative research design was employed, utilizing Importance-Performance Analysis (IPA) to assess the perceived importance and performance of three integrated learning models: Learning from Experience, Social Learning, and Formal Learning. Data were collected from 382 employees using surveys based on a 1-5 Likert scale. The results indicate significant gaps in the integration of explicit knowledge, particularly in the Learning from Experience and Social Learning models. These models were found to lack sufficient structures for organizing and disseminating explicit knowledge, which hindered their effectiveness. The study recommends the development of a centralized knowledge management system, standardized documentation guidelines, and enhanced collaborative learning environments to address these gaps. This research contributes to the theoretical understanding of the SECI model in public sector learning environments and offers practical insights for improving knowledge management strategies. The findings provide valuable implications for policy and decision-making, aiming to optimize learning processes and enhance organizational performance in public sector institutions.